The 2018–2023 drought in Berlin: impacts and analysis of the perspective of water resources management - I. Pohle; S. Zeilfelder; J. Birner; B. Creutzfeldt (Natural Hazards and Earth System Sciences)
The years 2018 to 2023 were characterised by extreme hydrometeorological conditions, with record-high average annual air temperatures and record-low annual precipitation across large regions of Europe. Berlin, the capital of Germany, is potentially vulnerable to drought conditions due to its location in a relatively dry region with relatively high water demand and complex water resources management in the Spree and Obere Havel catchments. To address the impacts of the 2018–2023 drought, various water resources management measures were implemented in Berlin and in the Spree and Obere Havel catchments.